A new species of the cicada genus Semia Matsumura, 1917 (Hemiptera: Cicadidae) from Vietnam, with a key to the species of the genus - Pham, Hong-Thai; Constant, Jerome (Zootaxa, 2013)
A new species of cicada, Semia gialaiensis, is described from Kon Ka Kinh National Park in central Vietnam. Photos of the adult, illustrations of the male genitalia, a distribution map and biological data are provided. A key to the species of Semia based on the male adults is also given.